Impact of Growth Mind-Set on University Students’ Psychological Well-Being - Ali, Shaukat; Zarar, Naila; Siddiqui, Ghazal Khalid (Annals of Human and Social Sciences, 2023)
This study was a Quantitative endeavor which was done to investigate the impact of Growth Mind-set on university students’ Psychological Well-Being. A number of studies have argued that there are evidences of the positive effect of the growth mindset on the students’ performance in academics. The growth mindset causes the motivation in students regarding their studies and performance. The literature shows the grey area related to the topic understudy within Pakistani context. This was the reason behind this study to be conducted. The population of this study includes the university students based in Punjab Province of Pakistan. The sample for the study comprised on 320 BS Education students studying in four universities who have been selected conveniently. The students’ Growth Mind-Set has been measured with the help of a Close-ended Questionnaire comprising 20 whereas the students’ Psychological Well-Being has been measured with the help of a scale comprising eight items. The results revealed a significantly high impact of Growth Mind-set on students’ Psychological Well-Being. It has been recommended that the teachers should deploy such techniques of teaching which promotes the growth mindset in the students so that they could be well-being as it has been shown by the researches that a positive relationship has been found between the psychological well-being and the students’ academic achievement.